2000
DOI: 10.1007/s002130000387
|View full text |Cite
|
Sign up to set email alerts
|

The P300 brain potential is reduced in smokers

Abstract: Rationale: Tobacco smoking is the most prevalent type of substance abuse, yet its biobehavioral etiology is little understood. Identification of differences between smokers and non-smokers on basic characteristics of neurocognitive functioning may help to elucidate the mechanisms of tobacco dependence. Objectives: This study assessed the relationship between smoking status and the P300 component of event-related potential (ERP) while controlling for potential confounders such as alcoholism, drug abuse, and psy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

7
69
2
1

Year Published

2000
2000
2014
2014

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 117 publications
(79 citation statements)
references
References 22 publications
7
69
2
1
Order By: Relevance
“…The obtained result is in good accordance with the majority of human ERP studies focusing on nicotine effects on the P300 component during sensory information processing (Polich and Ochoa 2004;McDonough and Warren 2001;Anokhin et al 2000). However, contrary to our results, in a large study by Anokhin et al (2000), P300 amplitudes (Pz) of former smokers were not significantly different from those of never smokers. This inconsistency might be due to several differences in study designs.…”
Section: Discussioncontrasting
confidence: 51%
See 1 more Smart Citation
“…The obtained result is in good accordance with the majority of human ERP studies focusing on nicotine effects on the P300 component during sensory information processing (Polich and Ochoa 2004;McDonough and Warren 2001;Anokhin et al 2000). However, contrary to our results, in a large study by Anokhin et al (2000), P300 amplitudes (Pz) of former smokers were not significantly different from those of never smokers. This inconsistency might be due to several differences in study designs.…”
Section: Discussioncontrasting
confidence: 51%
“…First, visual modality had been used, while in the present study, auditory stimuli were applied. Second, Anokhin et al (2000) drew their data from the Collaborative Study on the Genetics of Alcoholism with several alcohol-dependent subjects, while in the present study, axis I/ II diagnoses were excluded.…”
Section: Discussionmentioning
confidence: 99%
“…Twin research studies have yielded evidence of common genetic factors underlying pairs of disorders within this spectrum (Grove et al, 1990;Pickens, Svikis, McGue, & LaBuda, 1995;Slutske et al, 1998). Moreover, recent large-scale epidemiological studies with twins have shown that the broad externalizing factor, reflecting the shared variance among disorders of this type, is substantially (>80%) heritable (Kendler, Prescott, Myers, & Neale, 2003;Krueger et al, 2002;Young, Stallings, Corley, Krauter, & Hewitt, 2000).Of particular relevance to the current study is growing evidence that reduced P300 response is associated with other disorders in the externalizing spectrum besides alcohol dependence, including drug dependence (Attou, Figiel, & Timsit-Berthier, 2001;Biggins, MacKay, Clark, & Fein, 1997;Branchey, Buydens-Branchey, & Horvath, 1993), nicotine dependence (Anokhin et al, 2000;Iacono et al, 2002), child conduct disorder (Bauer & Hesselbrock, 1999a, 1999bKim, Kim, & Kwon, 2001), and adult antisocial personality Costa et al, 2000). Furthermore, reduced P300 is associated with risk for these other disorders as well as with active symptoms.…”
mentioning
confidence: 64%
“…For instance, a large number of studies have reported significantly reduced P3 amplitudes in abstinent alcoholic subjects when compared to non-alcoholic controls (e.g., Porjesz and Begleiter 1998) and in high-risk offspring of alcoholics when compared to matched low-risk control offspring (e.g., Begleiter 1984). Additionally, low P3 amplitudes are present in various disinhibitory conditions such as substance abuse (Herning 1996;Biggins et al 1997;Brigham et al 1997;Anokhin et al 2000;Iacono et al 2003), antisocial personality (Hesselbrock et al 1993;Costa et al 2000), conduct disorder (Iacono et al 2002) and attention deficit hyperactivity disorder (Klorman 1991;van der Stelt et al 2001). Low P3 amplitude has been observed in schizophrenia for the auditory modality in addition to a number of other disorders (c.f., Polich and Herbst 2000).…”
Section: Introductionmentioning
confidence: 96%